Getting the government America deserves how ethics reform can make a difference - Painter, Richard W., 1961- (Oxford : Oxford University Press, 2009)
This volume analyzes government ethics law from the perspective of an academic critic and that of a lawyer who was the chief White House ethics lawyer for two and a half years. Richard Painter argues that the existing ethics regime is in need of substantial reform.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political ethics -- United States